2009
DOI: 10.1089/fpd.2008.0255
|View full text |Cite
|
Sign up to set email alerts
|

Streamlined Analysis for Evaluating the Use of Preharvest Interventions Intended to Prevent Escherichia coli O157:H7 Illness in Humans

Abstract: The U.S. Department of Agriculture Food Safety Inspection Service is responsible for ensuring the safety of meat, poultry, and egg products consumed in the United States. Here we describe a risk assessment method that provides quantitative criteria for decision makers tasked with developing food safety policies. To demonstrate the utility of this method, we apply it to a hypothetical case study on the use of an Escherichia coli O157:H7 cattle vaccine to prevent human illness caused by consuming beef. A combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
(12 reference statements)
2
16
0
Order By: Relevance
“…In our study, the relationship between the number of human illnesses and vaccinated cattle was quite linear (R 2 = 0.99), similar to the model of Withee et al (2009). By comparison, we also modeled a reduction in concentration on/in carcasses/ feces as well as prevalence of shedders due to vaccination (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In our study, the relationship between the number of human illnesses and vaccinated cattle was quite linear (R 2 = 0.99), similar to the model of Withee et al (2009). By comparison, we also modeled a reduction in concentration on/in carcasses/ feces as well as prevalence of shedders due to vaccination (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Figure 2 and Table 3 show the relationship between the predicted number of human cases of O157 and the number of feedlot cattle vaccinated (termed ''production function'' in Withee et al, 2009). The model demonstrated that the number of human illnesses attributed to consumption of O157-contaminated ground beef can be greatly reduced by vaccination.…”
Section: Reduction In Human Illnesses Due To Vaccinationmentioning
confidence: 99%
“…If a positive correlation exists between the prevalence of contaminated carcasses and the levels of Salmonella on contaminated carcasses, then the assumed independence leads to conservative estimates of the reduction in illnesses associated with a reduction in prevalence. A similar assumption was explained with respect to Escherichia coli O157 and beef previously (Withee et al, 2009). …”
Section: Estimation Of Illnesses Avoidedsupporting
confidence: 69%
“…(1), (3), (5), (13)(14)(15)(16), (25)(26)(27), (36), (38), (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) Improvement in human or animal health or well-being, e.g.…”
Section: One Health Benefitsmentioning
confidence: 99%